Edukasi PHBS (Perilaku Hidup Bersih dan Sehat) di Pondok Pesantren - Wijayanti, Nor; Sularsih Endartiwi, Sri; Ispandiyah, Woro (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
CHLB (Clean and Healthy Living Behavior) enables the Islamic boarding school community to independently and actively participate in disease prevention and improve health and hygiene within the school environment. Observations at this Islamic boarding school revealed that approximately 70% of female students have not yet properly implemented CHLB.   For example, still reusing dirty clothes, not washing their hair at least once every 2 days, not combing their hair diligently, not washing their hands with soap and running water after using the toilet, still hanging dirty clothes, and brushing their teeth sometimes only once a day. Based on the results of interviews with students, it was also obtained information that some students had suffered from scabies, tinea versicolor, itchy skin, insect bites such as tomcats, and head lice. This activity aims to increase the knowledge and understanding of students about the importance of CHLB and its application in daily activities. The method used is education aimed at students who live at the Harun Asy-Syafi'i Putri Tahfidz Al-Qur'an Islamic Boarding School using the lecture method. The activity went smoothly. Students who participated in CHLB education activities at the Islamic boarding school had increased knowledge from before the education was held. Students already understand the importance of implementing CHLB in daily life to prevent disease. Every student is expected to consistently practice CHLB  at the Islamic boarding school. Furthermore, both students and Islamic boarding school administrators can always seek information to increase their knowledge of CHLB.